GIRL CHILD EDUCATION IN RURAL RAJASTHAN - Choudhary, Hari Ram (PEOPLE: International Journal of Social Sciences, 2019)
In today’s competitive world education is a necessity. Education for women is even more significant as she plays a crucial role in nurturing the society. While checkup the data of literacy rate in India (74.04%), women scores only 65.46% (census, 2011). Girls tend to show higher dropout rates than boys. School dropout rate among adolescent girls is also high (63.5%) (MoSPI, 2012). Rajasthan is known for low girl child enrolment and retention in all levels. Especially in the state of Rajasthan, the birth of girl child not welcomed as it does with boys. Discrimination on the basis of gender is common in school and home. Keeping the above context in perspective, the present study tries to identify the available institutional mechanism for promoting girl child education in rural Rajasthan and factors that contribute to dropping out of a girl child at the secondary or higher secondary level. The study is descriptive in nature focusing on girls who are enrolled in govt. schools of the villages in secondary or higher secondary level especially in Kishangarh block of Ajmer district. The Findings clearly indicates discrimination faced by girls in getting quality education at all levels.